Cap Precision in Perimiter Control Blasting and the Potential Application of Electronic Detonator - Derek T. Novotny (International Society of Explosives Engineers, 1998)
Blasting cap precision is of major importance to advanced blast design. New technologies have introduced the use of microchips within detonator casings in the hope that the electronic control of the timing element will increase the accuracy of the cap and therefore improve the results of perimeter control blasting applications. The electronic detonators have proven to be accurate in timing tests done to date. They boast cap scatter results to microsecond accuracy, but the question is, does this degree of accuracy actually prove to be beneficial during practical use in the industry, or are conventional technologies applicable.